ANALISA UNJUK KERJA BIODIESEL KAPUK RANDU - Seno Darmanto (TRAKSI, 2010)
This research is carried out to analyze the production of ceiba petandra biodiesel and performance examination in diesel engine. Production of ceiba petandra biodiesel is carried out with transesterification method and alkali catalyst. Transesterification reaction uses methanol and NaOH catalyst. The performance examination is carried out with engine test bed. Engine test bed consists of diesel engine, generator, load and instrumentation. Production of ceiba petandra biodiesel by transesterification method shows the conversion of ceiba petandra biodiesel reaches 90% in condition 50oC – 55oC and material composition consist of 80% of ceiba petandra oil, 20% of methanol and 2 gram NaOH per 100 ml methanol. The performance examination in engine test bed with biodiesel of ceiba petandra shows efficiency reach about 20% to mixture of biodiesel B5 and B10. Key word: ceiba petandra, transesterification, biodiesel and efficiency.